Perlunya Regulasi Terhadap Peraturan Penggunaan Ganja di Indonesia Ditinjau dari Kepentingan Medis - Fauziyah, Wiwin (Jurnal Panorama Hukum, 2022)
Cannabis is included in class in narcotics which is regulated in the Law of he Republic Indonesia Number 35 of 2009 concerning Narcotics. A number of countries have legalized cannabis as a medical treatment, but this is still being debated in Indonesian. This article discusses the need for regulation of the use of cannabis in Indonesian for medical purpose. This study uses library research with a normative approach. The government needs to rearrange regulations related to cannabis plants which are grouped in group I with medical conciderations.Â